Decoding AI art: from motivation to manifestation - Salimbeni, Guido (2025)
This thesis explores the integration of Artificial Intelligence (AI) art into artistic practices from an HCI and practice-led perspective. It centres on understanding the 'why' behind AI art practice, moving beyond technical implementations to explore the underlying stated motivations and conceptual goals driving artists to engage with AI technologies. The research employs methods primarily from Human-Computer Interaction (HCI) and practice-led research, drawing on theoretical analysis and critical reflection.